(untitled) (Journal of Contemporary Issues in Accounting, 2023)
This work examined the import of monetary policy on economy of aggregates in Nigeria. The impact of monetary policy on aggregate economy in Nigeria has always been subject of controversy owing to its implementation coupled with conflicting empirical finding. Specifically, this study examined the effect of monetary policy rate; cash reserve ratio, liquidity ratio and money supply which are the independent variables on the dependent variables (inflation and employment rate). The study adopted an ex-post facto research design using the Error Correction Mechanism (ECM) Model as a method of estimation. The result of the analysis revealed that there is a negative insignificant relationship between monetary policy instruments: monetary policy rate, cash reserve ratio, liquidity ratio and money supply on selected macro-economic variables: inflation and unemployment rate. The study concludes that Central Bank of Nigeria’s monetary policy adjustments have not facilitated improved macroeconomic variables in Nigeria. The work recommended among others that more awareness should be created in rural areas to boast financial inclusion; and that there should be synergy between the monetary policy and the fiscal policy managers. Equally Government should direct effort towards improving the level of development of both the money and capital market.